Calcinosis in childhood limited cutaneous systemic sclerosis. - Garofalo, L.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2008)
Although observable in other connective tissue diseases, calcinosis is characteristic of systemic sclerosis, particularly of limited cutaneous form, characterized by limited skin involvement, mainly of the hands and face, minor systemic involvement and slower progression; often anticentromere antibodies are present. Calcinosis is the first of the 5 signs of the acronym C.R.E.S.T. -Calcinosis, Raynaud, Esophagus, Sclerodactyly, Telangectases-, which has been today abandoned because the five signs are not always simultaneously present. Calcinosis is an invalidating complication as it can limit the joint mobility and cause pain. Many treatment have been proposed for calcinosis such as diltiazem, minocycline, CO2 laser and lithotripsy with contrasting results.